2020
DOI: 10.1523/jneurosci.2533-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone Attenuates Reward-Seeking Behavior and Increases Anxiety via D2 Receptor Signaling in Ventral Tegmental Area Dopamine Neurons

Abstract: Corticosteroids (CORT) have been widely used in anti-inflammatory medication. Chronic CORT treatment can cause mesocorticolimbic system dysfunctions, which are known to play a key role for the development of psychiatric disorders. The VTA is a critical site in the mesocorticolimbic pathway and is responsible for motivation and reward-seeking behaviors. However, the mechanism by which chronic CORT alters VTA dopamine neuronal activity is largely unknown. We treated periadolescent male mice with vehicle, 1 d, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 66 publications
1
20
0
Order By: Relevance
“…Chronic CORT treatment induces a variety of behavioral deficits, from anxiety-related phenotype ( David et al., 2009 ) to impaired positive valence behaviors ( Dieterich et al., 2019 ; Gourley et al., 2008 ; Moda-Sava et al., 2019 ). Consistently, we showed that 7-day CORT treatment decreased food-seeking behavior in a mildly risky environment, which is possibly be explained by elevated anxiety ( Peng et al., 2021 ). However, we did not observe any depressive-like phenotypes, which is reported in mice with 21-day CORT treatment ( Moda-Sava et al., 2019 ).…”
Section: Before You Beginsupporting
confidence: 65%
See 3 more Smart Citations
“…Chronic CORT treatment induces a variety of behavioral deficits, from anxiety-related phenotype ( David et al., 2009 ) to impaired positive valence behaviors ( Dieterich et al., 2019 ; Gourley et al., 2008 ; Moda-Sava et al., 2019 ). Consistently, we showed that 7-day CORT treatment decreased food-seeking behavior in a mildly risky environment, which is possibly be explained by elevated anxiety ( Peng et al., 2021 ). However, we did not observe any depressive-like phenotypes, which is reported in mice with 21-day CORT treatment ( Moda-Sava et al., 2019 ).…”
Section: Before You Beginsupporting
confidence: 65%
“…Although sulpiride reduced post reinforcement pause ( Figure 9 B), our analysis did not show that sulpiride normalized motivation in CORT mice ( Figures 9 A and 9C), except that it restored the reduced rear beam break rate ( Figure 9 E), which was constructive in interaction with the reward zone. Instead, Peng et al. (2021) found that intra-VTA sulpiride alleviated anxiety-like behavior using the elevated plus maze (data not shown here).…”
Section: Expected Outcomesmentioning
confidence: 56%
See 2 more Smart Citations
“…In addition to producing motivation deficits, a 7-day corticosterone treatment has been found to also alter VTA DA-ergic activity, decreasing excitatory synaptic transmission ( Peng et al, 2021 ). Intra-VTA administration of the D2 receptor antagonist sulpiride was found to restore excitatory transmission in the VTA but failed to rescue operant performance in a PR test, delineating a complex relationship between DA-ergic VTA activity and effort-related behavior.…”
Section: Depression and Stress-related Psychopathologymentioning
confidence: 99%